Persons in a court. Terms of persons in divorce matter by the example of Napoleonic Code’s translation - Wismont, Magdalena (Philology as the Ordering of Chaos: Language and Text Studies. Ad honorem Professoris Marci Cybulski, 2018)
The article presents conclusions concerning the formation Polish legal terminology in first half of the 19th century after introduction Napoleonic Code as a law validity in Duchy of Warsaw. The analysis oscillates about nomenclature of persons in divorce matter. There is a vocabulary which names representatives of public authorities (judicial and others) and persons who don’t represent any institution (for example interested parties in divorce matter and persons related with them). Researches demonstrated ways of accommodation Polish language to new legal conditions.